Assessment on marine litter ingested by fish in the Adriatic and NE Ionian Sea macro-region (Mediterranean). (August 2018) - Anastasopoulou, Aikaterini; Kovač Viršek, Manca; Bojanić Varezić, Dubravka; Digka, Nikoletta; Fortibuoni, Tomaso; Koren, Špela; Mandić, Milica; Mytilineou, Chryssi; Pešić, Ana; Ronchi, Francesca; Šiljić, Jasna; Torre, Michele; et al.
Abstract: This study presents data on the marine litter occurrence in the stomachs of fish species living in different marine habitats for the Adriatic and NE Ionian Sea macro-region. "Macro-litter" was examined in 614 specimens belonging to 11 species, while micro-litter in 230 specimens belonging to 7 species. The study highlights for the first time the presence of litter in the stomachs of the fish species Citharus linguatula . The occurrence of "macro-litter" in the guts of fish was <3% in both the NE Ionian and N Adriatic but reached 26% in the S Adriatic Sea. Micro-litter occurrence was 40 for the NE Ionian and increased to 87% in the N Adriatic (Slovenian Sea). The ingested "macro" and micro-litter differed among the areas. The marine habitat was found to affect the "macro"-litter ingestion but not the micro-litter. Highlights: First record of marine litter ingestion by the fish Citharus linguatula "Macro-litter" ingestion varied between areas and marine habitat. Micro-litter ingestion varied between areas but not between marine habitat.